Surface roughness and material removal models for magnetorheological finishing. (1st January 2013) - Kum, Chun Wai; Sato, Takashi; Wan, Stephen
This paper presents an experimental approach to verify the surface roughness and the material removal models previously proposed by Wan et al. The purpose is to adapt the models to be used for magnetorheological finishing (MRF). Experiments were carried out to verify the models for different tool revolution and different tool-to-surface gaps. Based on the experimental results, the surface roughness and material removal are found to be strong functions of the tangential force, but not of the coefficient of friction. New surface roughness and material removal model whereby the coefficient of friction is omitted are therefore proposed. In the proposed models, the surface roughness and material removal are written as a function of the work done by tangential force. The proposed models provide a better agreement to the experimental data in comparison to the original model by Wan.